Histopathological evaluation of treatment with chondroitin sulphate for osteoarthritis induced by continuous immobilization in rabbits - Torelli, SR; Rahal, Sheila Canevese [UNESP]; Volpi, R. S.; Sequeira, Julio Lopes [UNESP]; Grassioto, I. Q. (Blackwell Verlag Gmbh, 2005)
The aim of this study was to evaluate histologically the action of chondroitin sulphate in osteoarthritis experimentally induced by continuous immobilization. Fourteen young female Norfolk rabbits aged 2.5-3 months at the beginning of the experiment were divided into two equitable groups submitted to immobilization of the right knee for a period of 12 weeks. The treated group received 1.0 ml/animal/s.c. of 12% chondroitin sulphate, once a week for 12 weeks, and the untreated group did not receive any treatment. Two additional animals were not submitted to knee immobilization (sham group). Microscopical examination of knee preparations stained with haematoxylin-eosin and Masson trichrome showed lesions of both joints in treated and untreated groups, with no significant difference between the scores obtained for the right and left knees. Examination of preparations stained with picrosirius red showed collagen fibre alignment and misalignment in the right and left knees of the animals of all groups, but statistic analysis could not be performed. It was not possible to differentiate the proteoglycan concentration between limbs or groups (treated and untreated) by safrtanin O or toluidine blue staining. It was possible to conclude that the chondroitin sulphate was not able to reduce the histological changes induced by this osteoarthritis experimental model.